Auditory P300 event-related potentials in children with Sydenham's chorea - Ozdemir, Hasan Huseyin; Demiroren, Kaan; Demir, Caner F.; Serin, Mine Hapsen (Assoc Arquivos Neuro- Psiquiatria, 2014)
P300 event-related potentials (ERPs), objective measures related to cognitive processing, have not been studied in Sydenham's chorea (SC) patients. Purpose: To assess cognitive impairment with P300 ERPs. Method: Seventeen patients with SC and 20 unaffected healthy children were included. Stanford-Binet test was used for psychometric assessment, and odd-ball paradigm was used for auditory ERPs. Results: There was no significant difference in P300 latencies between the SC-pretreatment group, SC-posttreatment group and control group (p>0.05). Mean interpeak latencies in SC-pretreatment group and SC-posttreatment group showed significant prolongation compared with the control group (p<0.05). Mean interpeak latencies in SC-posttreatment group were significantly decreased compared with SC-pretreatment group (p<0.05). Compared to controls, patients did not show significant difference in Stanford-Binet intelligence examination. Conclusion: This report suggests that interpeak latencies and amplitudes of P300 ERPs could be useful for detecting and monitoring cognitive impairment in SC patients.
Potenciais auditivos evento-relacionados à P300 em crianças com coreia de Sydenham
Keywords: Sydenham's chorea; cognitive function; event-related potentials